STUDI PERENCANAAN PENGENDALIAN WAKTU PELAKSANAAN PADA PENGEMBANGAN KAWASAN RUMAH SEWA KECAMATAN TENGGARONG - ANNISA, FITRI (KURVA S JURNAL MAHASISWA, 2016)
Controlling time is process determination accomplished, evaluation work, and improvement  if  necessary. Success or failure of  the project caused by not maxsimal planning and insufficiently effective controlling, so that the project activity is inefficient.  As the consequences of these impact suffered project delay, decreasing of quality, and increasing performing cost.Planning controlling time with method of Critical Path Methode is one of way management that can use for planning and controlling duty in project that can show current time planning and activity between project. So also with Microsoft project we could take controlling  of finance and tracking fitur buget, therefore we can assign performing cost to project and program duty. Therefore, we can know the planning execution time by using both methods.In this study writes attempt to describe and explain how process planning controlling time of development distric rent house tenggarong used both method. The result showed the optimal duration of the planned 180 day experience many critical timing needs to optimized back.